Chastity on the early modern English stage, 1611-1649 - Lander, B (2014)
‘Chastity on the Early Modern English Stage’ seeks to explain the relationship between tragicomedy’s brief and short-lived English popularity and the royal cult of chastity which spanned exactly the same historical time-frame. This study attempts to define a cultural movement which influenced the political, religious, social, intellectual, aesthetic, and medical fields in the first half of the seventeenth-century and argues that the narrative tropes which structured, and assisted the spread of, the post-Elizabethan cult of chastity were the same tropes governing the tragicomedies so popular in the period. The arguments made for tragicomedy are speculatively extended to all generic forms, with the intention of expanding an area of scholarship still dominated by formalist analysis. By focussing on narrative tropes and locating them within both fictional and non-fictional texts and in the presentation and discussion of significant events (from medical discoveries to liturgical arrangements and royal birthing rituals) this thesis aims to illustrate that the human and cosmic visions articulated by different dramatic genres were as relevant to early modern lives outside the theatre as they were to those within it. Genre is thus less a description of a text’s formal characteristics and more a set of truths governing certain human experiences both in texts and in life. Focussing on Shakespeare’s The Winter’s Tale, two plays by John Ford, Caroline court masques and birthing rituals, Milton’s A Maske and a number of non-professional performances (from the Earl of Castlehaven’s trial to William Harvey’s demonstration of the circulation of the blood), ‘Chastity on the Early Modern English Stage’ describes the four tropes of chastity and their place in tragicomic experience from the death of Elizabeth I to the beheading of Charles I. While Charles’s death and the closure of the theatres are crucial reasons for the abrupt end of the cult of chastity and tragicomedy, this thesis argues that cause must also be attributed to the efforts of pro-Parliamentary and Puritan writers who, throughout the 1630s and 1640s, sought to claim the tropes of chastity for their own rhetoric and cause. Their success resulted in a redefinition of chastity as masculine, individuated, Parliamentarian, Protestant, intellectual, civic and prosaic instead of Catholic, royal, spectacular, feminised, Marian, pietised, and theatrical.